(untitled) (Global Journal of Science Frontier Research, 2016)
Origins of dark energy and inflation in semiclosed Friedman model universe are sought by examining the imaginary pair of gravitationary bound Planckeon-Higgs boson composite requiring temperature T 10 15 K for thermal creation. Inflation is likely to be related to the singular nature of the transition amplitude D(s 2 ) of the Higgs boson obeying PC-and T-symmetric Klein-Gordon equation, between neighboring points separated by a space like distance s 2 = (ct) 2 -r 2 < 0 in the ultraviolet region outside the light cone, past and future, violating time-symmetry and local causality.